Getting Cozy with the Zombie Apocalypse: The Saferoom as Capitalist Breakroom in "Left 4 Dead" and "Back 4 Blood" - Smith, Caighlan (Replay. The Polish Journal of Game Studies, 2024)
This article considers how players experience coziness inside t h e saferooms of Left 4 Dead, Left 4 Dead 2, and Back 4 Blood, which are ot herwise high-demand, fast-paced first-person shooter zombie games. Pairing Agata Waszkiewicz and Martyna Bakun’s concept of “situational coziness” with James Ash’s “intense space,” this discussion first explores how moments of coziness can occur within competitive and stressful FPS environments, and indeed may be considered cozy specifically in how they afford temporal, spatial, aesthetic, and audial reprieves from the stress of those environments. I explore how such situational coziness, when produced as both break from and reward for succeeding at stressful zombie apocalypse gameplay, contributes to the zombie genre’s ability to allow players performances of an idealized iteration of capitalism’s work/ leisure cycle, as both “work” and “leisure” have come to be defined under and in service to exploitative capitalist labor conditions.